Evaluation of the Department of Planning and Infrastructure's Bike to Work Breakfast 2005 - McManus, Alexandra; McManus, Jennifer; McDonald, E.; McDonald, M. (Western Australian Centre for Health Promotion Research, Curtin University, 2005)
The Metropolitan Transport Strategy (1995) proposed moving from a transport system which was dominated by low occupancy car use, to a more balanced transport system of public transport and non-motorised transport options. Creating this change requires initiatives that create critical mass awareness, in work organisations and the community. The Bike to Work Breakfast is an example of such an initiative. This year it was held on Friday 11 March, 2005 and aimed to increase awareness of, and promote cycling as an alternative mode of transport to and from work. A free healthy breakfast was provided to everyone who cycled on the day. A total of 1232 participants who attended the 2005 Bike to Work Breakfast completed questionnaires. The majority of respondents were male (69%, n=845). The age of respondents varied, with the most common age group being 31-40 years (29%, n=353) followed by 41-50 years (26%, n=324). Respondents cited a number of different reasons for cycling. The majority indicated improved fitness (84%, n=1035) and enjoyment (63%, n=777) as the main reasons for cycling. Almost half of respondents (43%, n=535) cycled on a daily basis whilst a further 42% (n=524) reported cycling 2-3 times per week. Fifty three percent of respondents (n=5595) lived less than 13 kilometres from work and almost one quarter (24%, n=266) lived less than eight kilometres from their workplace. Respondents suggested they would ride to work more often if there were showers at work (34%, n=422), more on road facilities (29%, n=360) and lockers at work (24%, n=293). Of the 1232 participants who completed questionnaires, sixty eight percent (n=843) had attended the Bike to Work Breakfast previously.